FORMATION OF HARMFUL BIOTA IN WINTER RYE AGROCENOSES IN THE UKRAINIAN POLISSIA - Kliuchevych, М. М.; Stoliar, S. H.; Hrytsenko, O. Yu.; Bilotserkivska, L. V. (Scientific Progress & Innovations, 2020)
Grain farming is a main industry of plant production that provides the population with food products, an- imal husbandry with fodders and the industrial sector with raw materials. Winter rye, which is one of the most widespread cereal crops, is characterized by high edible and feeding qualities. The crop has a high po- tential productivity, however in recent years a decrease in its yield has been observed. Obtaining high yields is impeded by the spreading of pests in winter rye agrocenoses. The agrocenoses of winter rye were exam- ined in the conditions of the Ukrainian Polissia between 2016 and 2019, and their phyto-sanitary state was established. The species composition of pathogenic agents of fungal diseases and crop phytophages was de- termined. Field studies of the species composition of pests were conducted in the experimental field of Zhy- tomyr National Agro-Ecological University by cultivating crops in organic rotation (vetch and oat mix – winter rye – field beans – white mustard – winter spelt – buckwheat). As a result, it was found out that the main share in the structure of crop mycoses in the Polissia belonged to Puccinia recondite Dietel & Holw. (35 %), Bipolaris sorokiniana (Sacc.) Shoemaker (23 %) and fungi of the Fusarium spp. genus (20 %). The spreading of fungal diseases in agrocenosis varied from 29.7 to 68.5 %. Wheat leaf rust (65.6 %), common root rot (58.7 %) and Septoria blight (38.4 %), were the most widespread while powdery mildew (27.5 %) and fusarium root rot (32.8 %) were the least widespread. The degree of mycoses development ranged from 4.2 to 20.3 %. The plants were mostly affected by wheat leaf rust (20.3 %) and common root rot (15.7 %), and least affected by powdery mildew (4.2 %) and Septoria blight (7.5 %). It should be noted that in the re- cent years under considerable climate change, there has been mass reproduction, intensive migration and spreading of insects in agrocenoses. The results of the conducted studies of winter rye crops have shown that agrocenoses are characterized by high colonization of major pests during the growing season, which re- quires mandatory application of plant protection means. Pest colonization of agrocenoses varied from 8.7 to 21.8 %. The areas were colonized by the barley flea beetle (21.8 %) and Oscinella (15.7 %) most of all and by leafhoppers – the least (8.7 %). The conducted investigation concerning the spreading and development of mycoses, pest colonization and weed infestation of the sown areas will contribute to the development and substantiation of environmentally friendly protection systems that will provide high yields of safe grain products and reduce pesticide load on agro-ecosystems.